Case Report: Laparoscopic vaginoplasty in a case of partial androgen insensitivity syndrome and a literature review of 16 cases in China - Qin, Haixia; Liu, Huaqian; Liu, Qiang; Li, Baiou (Frontiers in Surgery, 2025)
BackgroundWe examined the clinical features, diagnosis, treatment, and future gender choice of patients with partial androgen insensitivity syndrome (PAIS).Case presentationThe clinical features, specialty examinations, three-stage surgical examination, and treatment process of a patient with PAIS were comprehensively reviewed. Additionally, 16 PAIS case reports were collected from Chinese databases and analyzed. Seventeen PAIS cases were included in this study. All patients presented with primary amenorrhea (17/17) and displayed specific clinical features such as a male social identity or appearance (3/17), an underdeveloped phallus or clitoromegaly (16/17), abnormal urethral development (7/17), and breast development (4/17). Twelve cases were managed as women, both surgically and with hormone replacement therapy. The patient in this case report underwent three surgical procedures involving laparoscopic examination and clitoroplasty, left orchidopexy, and laparoscopic vaginoplasty using peritoneum and an acellular dermal matrix.ConclusionsPAIS is a rare disorder of sex development (DSD) with a 46,XY karyotype and is a congenital X-linked recessive disease. Therefore, a deeper understanding of the pathogenesis of androgen insensitivity syndrome allows more accurate diagnosis, personalized treatment, and organized follow-up of the condition, thereby avoiding gender dysphoria.